Training Program Management: Study of the Handmade Training Program at PKBM Rumpun Aksara - Setiyani, Gayuh; Hendrawijaya, A.T; Hasan, Fuad (Indonesian Journal of Adult and Community Education, 2023)
This research aims to find out and describe how the handmade training program is managed at PKBM Rumpun Aksara. This research uses descriptive research with a qualitative approach. The research location was located at PKBM Rumpun Aksara Panti Jember using purposive area techniques. The technique for determining informants uses Purposive Sampling. Data collection techniques use observation, interviews and documentation. The data validity checking techniques used are increased persistence, extended observations and triangulation in the form of source triangulation and technical triangulation. Data analysis uses Miles and Hubarman's theory by collecting data, reducing data, presenting data, and verifying data. The research results show that planning activities in handmade training at PKBM Rumpun Aksara are carried out in a structured and systematic manner, starting from identifying needs, to making learning lesson plans, as well as determining the methods and media carried out by the training instructor. The activities for implementing the handmade training program have been running according to the plans that have been determined. Meanwhile, evaluation activities for handmade training include holding meetings with instructors to discuss program implementation. Meanwhile, evaluation of learning residents involves assessing the process, results, level of interest of learning residents and the impact of handmade training on learning residents.